Increased Risk of Nasopharyngeal Carcinoma with Increasing Levels of Diet-Associated Inflammation in an Italian Case–Control Study. (2nd October 2016) - Shivappa, Nitin; Hébert, James R.; Zucchetto, Antonella; Montella, Maurizio; Libra, Massimo; Garavello, Werner; Rossi, Marta; La Vecchia, Carlo; Serraino, Diego
ABSTRACT: Purpose: Components of diet can modulate inflammation and therefore may have an important role in the development of nasopharyngeal carcinoma (NPC). Little is known about the inflammatory potential of diet in relation to nasopharyngeal carcinogenesis. Methods: Data from an Italian multicenter case–control study conducted between 1992 and 2008 and including 198 cases with incident, histologically confirmed NPC, and 594 controls hospitalized for acute nonneoplastic diseases were used to estimate the relation between a dietary inflammatory index (DII) and the risk of NPC. The DII was computed based on the intake of selected dietary factors assessed by a validated 78-item food frequency questionnaire. Logistic regression models were used to estimate odds ratios (ORs) adjusted for study center, place of living, sex, age, year of interview, education, tobacco smoking, alcohol drinking, and energy intake using the residual method. Results: Subjects with higher DII scores had an increased risk of NPC, with each DII point increasing risk by nearly 20% [OR: 1.19; 95% confidence interval (CI): 1.05–1.36]. Compared to subjects in the lowest DII tertile, those in the highest tertile had >60% higher risk of NPC (OR: 1.64; 95% CI: 1.06–2.55; P trend = 0.04). Conclusion: These results indicate that inflammatory potential of diet plays a role in NPC.